RESPOSTA FISIOLÓGICA DE Salvinia biloba Raddi (Salviniaceae) EXPOSTA À HIDROQUINONA - ROCHA, Carina Machado,; SANTIAGO, Etenaldo Felipe,; ARRUDA, Gilberto José,; SANTOS, Jaqueline Silva, (ANAIS DO ENIC, 2023)
-